Changes in photosynthetic rate and physiological characters of Andrographis paniculata under different shade levels and pruning - Omar, Nur Faezah; Hassan, Siti Aishah; Ramlan, Mohd Fauzi; Megat Wahab, Puteri Edaroyati; Abdullah, Mohd Puad (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
The physiological aspects and growth pattern under different light intensities can affect the composition and quality of A. paniculata. The objective of this study was to determine the effect of shade level and method of pruning on photosynthetic rate and physiological characters of A. paniculata. A factorial experiment was arranged in split plot design with three replications. The following shade levels (%): 0, 20, 30 and 50 were the main plot while number of pruning: 0, 1 and 2 times were the sub plot. Data for photosynthetic rate, stomata conductance, transpiration rate and relative chlorophyll content were taken at 7th week of transplanting and leaf nutrient content was taken after harvesting. The leaf photosynthetic rate increased with increasing light intensity. A high photosynthetic rate was obtained when plant grown under full sunlight. Stomatal conductance was not affected by shades levels and number of pruning. Increasing shade levels significantly increased N and P elements in leaf. The results indicate that the different shade levels influenced photosynthetic rate and nutrient content of A. paniculata.